2013
DOI: 10.36095/banxico/di.2013.07
|View full text |Cite
|
Sign up to set email alerts
|

Access to Credit: Awareness and Use of Formal and Informal Credit Institutions

Abstract: In this paper we study the determinants of use of formal and informal credit sources. Given that awareness is a necessary step towards use of credit, in order to control for the possible selection bias we decompose the decision to use credit as a two stage decision process in which first, households form their choice set by deciding which type of institutions they want to consider as possible lenders (awareness), and then choose among them (use). Additionally, we allow for correlation between being aware of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
2
23
1
3
Order By: Relevance
“…Many existing literature on access indicates that financial access is not only about availability of institutions but also a synergy of both supply and demand sides (Claessens, 2005;. According to Campero and Kaiser (2013), the availability of financial products and services are determined by components of the supply side and at the same time, the usage of these products and services are driven by components of the demand side. In terms of financial inclusion, constrains in data had implied that components of the supply side were more studied than demand side components, requiring the availability of more comprehensive data in individual-level, and, as a consequence, the influence of individual-level determinants on access to formal sources of finance are initiating to be estimated.…”
Section: Factors Affecting Financial Inclusionmentioning
confidence: 99%
“…Many existing literature on access indicates that financial access is not only about availability of institutions but also a synergy of both supply and demand sides (Claessens, 2005;. According to Campero and Kaiser (2013), the availability of financial products and services are determined by components of the supply side and at the same time, the usage of these products and services are driven by components of the demand side. In terms of financial inclusion, constrains in data had implied that components of the supply side were more studied than demand side components, requiring the availability of more comprehensive data in individual-level, and, as a consequence, the influence of individual-level determinants on access to formal sources of finance are initiating to be estimated.…”
Section: Factors Affecting Financial Inclusionmentioning
confidence: 99%
“…One major indicator of financial inclusion is ownership of formal credit (Demirgüç-Kunt & Klapper, 2013). Formal credit refers to credit or loans issued from financial institutions that are regulated by the government and operated within the regulatory framework of the financial system (Campero & Kaiser, 2013). Studies have shown that a great number of individuals and families worldwide lack access to formal credit or do not use it Tejerina & Westley, 2007).…”
Section: Use Of Formal Creditmentioning
confidence: 99%
“…They may also prefer to deal in cash to avoid leaving traces in the financial system. 12 Campero and Kaiser (2013) show empirically for Mexico that households employed in the formal sector are 5.7 times more likely to use bank credit than those in the informal sector.…”
Section: Issues Beyond the Banking Sectormentioning
confidence: 99%
“…Financial education may still be lacking in some sectors of the economy and some regions of the country. More generally, Campero and Kaiser (2013) have shown that households with greater levels of schooling are more likely to be aware of credit sources (formal and informal) and that regions with greater average schooling levels are marked by greater use of formal credit.…”
Section: Issues Beyond the Banking Sectormentioning
confidence: 99%